The globalization of professional basketball: context and competition matters in the NBA, WNBA, and Olympics - Bartee, H. Jr. (The Sport Journal, 2024)
The role of professional basketball has evolved through the years given socio-historic and current perspectives involving the NBA, WNBA, and Olympics. Such perspectives have shaped the context and competition for globalization and the subsequent impact and implications for the broader basketball industry.